Bimbingan Keagamaan Melalui Pengajian Rutin Untuk Meningkatkan Kesadaran Beragama Masyarakat - Zhilla, Mu'thiyatul; Fajar, Dadang Ahmad; Mujib, Abdul (Irsyad: Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2023)
Some of teenagers did the wrong thing caused by lackness of their emotional skills. This research in order to know about the relation between parenting that used by boarding school with student’s emotional intelligence to recognize about their emotion, self motivating, their empathy and also the relationship between the other. However this research to know about how deep both of their relationship was. This research starts by quantitative research methodology with survey using questionnaire to 36 pupils of Al-Kasyaf orphanage. Random sampling is the technique that used, and the result, there is a relationship between them and significantly is about 0,048 with coefficient 0,331 or 33,1% and it shows that there is a low relationship between two variables. Emotional intelligence caused by external and internal factors.